Education, culture, and underdevelopment: Haiti’s tragic failure - von Feigenblatt, Otto Federico (Universidad y Sociedad, 2022)
The present study explores the role of national identity and nationalism in Haiti’s development woes. An applied anthropological perspective is adopted as a way to assess the role of cultural factors to interpret the many challenges faced by international organizations in terms of promoting sustainable development in Haiti. Several development paradigms are explored and the case studies of Singapore, Guadeloupe, China, Cambodia, and South Korea are used to provide alternative models of national development. The paper concludes that Haiti’s nationalism and the cultural relativism of many intergovernmental organizations and non-profit organizations dealing with Haiti have focused on superficial aspects of development at the expense of developing the human capital the country needs in order to escape the trap of dependency and underdevelopment. Keywords: International Development, Haiti, Culture, Education and Nationalism. RESUMEN El presente estudio explora el papel de la identidad nacional y el nacionalismo en los problemas de desarrollo de Haití. Se adopta una perspectiva antropológica aplicada como una forma de evaluar el papel de los factores culturales para interpretar los muchos desafíos que enfrentan las organizaciones internacionales en términos de promover el desarrollo sostenible en Haití. Se exploran varios paradigmas de desarrollo y se utilizan los estudios de caso de Singapur, Guadalupe, China, Camboya y Corea del Sur para proporcionar modelos alternativos de desarrollo nacional. El documento concluye que el nacionalismo de Haití y el relativismo cultural de muchas organizaciones intergubernamentales y organizaciones sin fines de lucro que se ocupan de Haití se han centrado en aspectos superficiales del desarrollo a expensas de desarrollar el capital humano que el país necesita para escapar de la trampa de la dependencia y el subdesarrollo. Palabras clave: Desarrollo Internacional, Haití, Cultura, Educación y Nacionalismo.